Relationships between employee socialization, in-role and citizenship behaviors, and organizational identification - Dzimidienė, Agnė; Bagdžiūnienė, Dalia (Psichologija, 2015)
Employee socialization is closely related to the wide range of positive attitudinal outcomes (Cooper-Thomas & Anderson, 2006; Saks & Gruman, 2011); however, less attention in the empirical studies is paid to the behavioral consequences. This study aims to analyze the relationships between employee socialization aspects, organizational identification, in-role and organizational citizenship behaviors, and to analyze the results in relation with the employee tenure. In particular, this study posits that, first, socialization aspects predict the in-role, citizenship behaviors and organizational identification and, second, identification moderates the relationships between employee socialization dimensions and in-role, and citizenship behaviors. The sample was composed of 129 non-managerial employees from private sector Lithuanian organizations. The following measures were included in the questionnaire: socialization scales (Chao’ O’Leary-Kelly, Wolf, Klein, & Gardner, 1994), prospects for the future scale (Taormina, 1994), the organizational identification scale (Mael & Ashforth, 1992), in-role (Williams & Anderson, 1991) and citizenship behavior (Bagdžiūnienė, Lazauskaitė-Zabielskė, & Urbanavičiūtė, 2013) scales. The hierarchical regression analysis revealed the following predictors for the socialization outcomes: for employees who work less than one year, citizenship behavior is predicted by history, language and politics, and organizational identification is predicted by goals and values; for employees working more than one year, citizenship behavior is predicted by goals and values, and organizational identification by future prospects. Performance proficiency predicts the in-role behavior in both subsamples. Organizational identification moderates the relationships between socialization dimensions and in-role, and citizenship behaviors: organizational goals and values, politics and future prospects predict the in-role behavior, and performance proficiency predicts citizenship behaviors when the level of organizational identification is high. The results prove the necessity to develop and systematically apply in organizations human resource management practices enhancing employee socialization and to analyze in-role, citizenship behaviors and organizational identification as the socialization success outcome indicators.
Keywords: employee socialization; in-role behavior; organizational citizenship behavior; organizational identification